Interest in following swimming training for achievement at club tirta alvita Yogyakarta - Suharjana Suharjana; Sumarjo Sumarjo; Muhamad Ichsan Sabillah; Ardhika Falaahudin (Jorpres (Jurnal Olahraga Prestasi), 2023)
Swimming is an achievement sport and recreational activity that aims to relieve mental stress by balancing physical and psychological conditions. The purpose of this study was to determine interest in participating in swimming training at Club Tirta Alvita Yogyakarta. The type of research used in this research is descriptive quantitative research. The population in this study were children taking swimming lessons at the Tirta Alvita Yogyakarta Club with a total of 21 athletes. The sampling technique in this study used a total sampling technique. The sample in this study amounted to 21 athletes. Data analysis in this study uses a Likert scale. Data analysis used in this research is quantitative descriptive statistical analysis. From the results of the study showed that the results of interest in swimming training with a percentage of "always" was 42.85% with a total of 9 athletes and a percentage of "often" was 57.14% with a total of 12 athletes. So it can be concluded that the category level of the percentage of interest in swimming achievement training at the Tirta Alvita Yogyakarta Club is in the moderate category with a percentage of 57.14%.